2022
DOI: 10.1001/jamanetworkopen.2022.9655
|View full text |Cite|
|
Sign up to set email alerts
|

Concordance of Clinician-Documented and Imaging Response in Patients With Stage IV Non–Small Cell Lung Cancer Treated With First-Line Therapy

Abstract: IMPORTANCEIn observational oncology studies of solid tumors, response to treatment can be evaluated based on electronic health record (EHR) documentation (clinician-assessed response [CAR]), an approach different from standardized radiologist-measured response (Response Evaluation Criteria in Solid Tumours [RECIST] 1.1). OBJECTIVE To evaluate the feasibility of an imaging response based on RECIST (IRb-RECIST) and the concordance between CAR and imaging response based on RECIST assessments, and investigate disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“… 36 In another case, Flatiron Health created an external reference standard of radiologist-measured response via RECIST 1.1 to validate clinician-assessed response on the basis of EHR documentation. 35 Although robust, such validations are often labor-intensive or infeasible.…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“… 36 In another case, Flatiron Health created an external reference standard of radiologist-measured response via RECIST 1.1 to validate clinician-assessed response on the basis of EHR documentation. 35 Although robust, such validations are often labor-intensive or infeasible.…”
Section: Reliabilitymentioning
confidence: 99%
“…34 Complex clinical concepts captured from unstructured data typically require a more robust validation process than variables that are structured data at the source. [35][36][37] For example, variables such as birth year or sex are commonly entered into structured fields to support clinical workflows and are expected to be verified at multiple points during care. Although verification of data processing and pipelines remains essential to data integrity, validation of such data against external references is less critical, given that the value is expected to be accurate and complete to support clinical procedures.…”
Section: Accuracy: Validation Approachesmentioning
confidence: 99%
“…Cancer therapy is based on histology combined with all imaging findings and the presence of local and distant metastases that should be regularly followed up for the progression of the disease. Screening in those cases assesses the need for a second or third line of therapy 7 . The restaging should be based on RECIST 1.1 criteria 8 .…”
Section: Comment On "Evaluation Of Pulmonary Nodules By Magnetic Reso...mentioning
confidence: 99%
“…11 This may lead to the potential for misclassification of the outcome and inability to properly estimate the effect size, as physician-reported response rate may overestimate response rate according to RECIST criteria in the real-world setting. 12,13 An externally controlled trial may underestimate the effect of the medical product if physician-reported response is used in the RWD-derived external control arm. Likewise, a postmarketing study may be interested in characterizing medical product effectiveness in patients who were underrepresented in the pivotal clinical trial, such as older adults.…”
mentioning
confidence: 99%